Severe anaphylactic reactions to glutamic acid decarboxylase (GAD) self peptides in NOD mice that spontaneously develop autoimmune type 1 diabetes mellitus - Steinman Lawrence; DeVoss Jason; Tsai Mindy; Sanna Maija; Pedotti Rosetta; McDevitt Hugh; Galli Stephen J (BMC Immunology, 2003)
Abstract Background Insulin dependent (i.e., "type 1") diabetes mellitus (T1DM) is considered to be a T cell mediated disease in which TH1 and Tc autoreactive cells attack the pancreatic islets. Among the beta-cell antigens implicated in T1DM, glutamic acid decarboxylase (GAD) 65 appears to play a key role in the development of T1DM in humans as well as in non-obese diabetic (NOD) mice, the experimental model for this disease. It has been shown that shifting the immune response to this antigen from TH1 towards TH2, via the administration of GAD65 peptides to young NOD mice, can suppress the progression to overt T1DM. Accordingly, various protocols of "peptide immunotherapy" of T1DM are under investigation. However, in mice with experimental autoimmune encephalomyelitis (EAE), another autoimmune TH1 mediated disease that mimics human multiple sclerosis, anaphylactic shock can occur when the mice are challenged with certain myelin self peptides that initially were administered with adjuvant to induce the disease. Results Here we show that NOD mice, that spontaneously develop T1DM, can develop fatal anaphylactic reactions upon challenge with preparations of immunodominant GAD65 self peptides after immunization with these peptides to modify the development of T1DM. Conclusions These findings document severe anaphylaxis to self peptide preparations used in an attempt to devise immunotherapy for a spontaneous autoimmune disease. Taken together with the findings in EAE, these results suggest that peptide therapies designed to induce a TH1 to TH2 shift carry a risk for the development of anaphylactic reactivity to the therapeutic peptides.